(untitled) (Journal of Applied Oral Science, 2008)
The aim of this study was to analyze the buccal tissue responses of Wistar rats to 2% chlorhexidine solution, calcium hydroxide and the association of both products. For this purpose, 30 specimens were randomly implanted in the filtrum of the four upper and lower hemiarches with a polyethylene tube containing one of the following substances: 2% chlorhexidine solution, calcium hydroxide and 2% chlorhexidine solution (test groups); calcium hydroxide and distilled water and distilled water (control groups). Ten rats each were distributed according to time interval of evaluation at 7, 15 and 30 days. The histological sections were stained with Harris hematoxylin and eosin. Analysis was performed with an optical microscope at x100, x200 and x400 magnifications by an expert examiner blinded to the materials. The sections were classified by scores attributed to inflammatory events and by a ranking determined according to the severity of the inflammation. The results of the inflammatory events and severity ranking were submitted to the Kruskal-Wallis test at a 0.05 level of significance. No statistically significant difference occurred among the tested materials; however, all materials showed a decreased of severity with respect to longer time intervals.